18alpha-Glycyrrhetinic acid inhibits the viability of HR5-CL11 cervical carcinoma cells through induction of apoptosis and DNA damage (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed to investigate the effect of 18α-glycyrrhetinic acid on induction of apoptosis and DNA-damage in HR5-CL11 cervical carcinoma cells. The results revealed 73.6% reduction in HR5-CL11 cell viability on treatment with 5 µM concentration of 18α-glycyrrhetinic acid for 48 hours. The DNA of 18α-glycyrrhetinic acid-treated cells showed a ladder-like pattern. Fragmentation of DNA in the 18α-glycyrrhetinic acid-treated cells was markedly higher compared to the control cells. Examination of the DNA damage in HR5-CL11 cells after treatment with 18α-glycyrrhetinic acid showed breakage in DNA strands and formation of comet-like structures. The frequency of comet formation in 18α-glycyrrhetinic acid treated cells was found to be 7.8 after 48 hours. The population of cells with more than four γH2AX foci was increased to 38.6% on treatment with 5 µM concentration of 18α-glycyrrhetinic acid. Thus, 18α-glycyrrhetinic acid inhibits the viability of HR5-CL11 cervical cancer cells through induction of apoptosis by DNA damage and can be used for the treatment of cervical cancer. Video Clip of Methodology:MTT assay: 1 min 13 sec   Click to watch